Select writings and speeches of Maulana Mohamed Ali : Vol. 2 - Ali, Mohamed, 1878-1931.; Iqbal, Afzal (Lahore : Shaikh Muhammad Ashraf, 1944)
On contemporary Indian politics.
Microfilm.
Keywords: India -- Politics and government -- 1919-1947.